The banning of anti-personnel landmines : the legal contribution of the International Committee of the Red Cross - Maresca, Louis; Casey-Maslen, Stuart (Cambridge University Press, 2000)
This book provides an overview of the work of the International Committee of the Red Cross to ban anti-personnel landmines from 1955 through 1999. It contains ICRC papers and speeches, the 1995-96 Review Conference of the 1980 Convention on Certain Conventional Weapons, and the Ottawa treaty banning anti-personnel mines.